北极海洋沉积物中锰细菌的分离与系统发育 - 林学政; 高爱国; 陈皓文 (2008)
对中国第二次北极科学考察采集的北极海洋沉积物中的锰细菌进行了筛选、分离和系统发育分析。根据其在筛选平板上菌落的形态学特征,分别从站位P11和S11采集的沉积物中分离到了21株和19株锰细菌。系统发育分析表明,两个站位的锰细菌群落组成有着明显的差别。站位P11分离的可培养锰细菌主要由细菌域(Bacteria)中变形杆菌门的γ-变形杆菌纲(γ-Proteobacteria)和放线菌纲(Actinobacteria)组成,二者分别占86%和14%;γ-变形杆菌纲主要包括嗜冷杆菌属(Psychrobacter)、希瓦氏菌属(Shewanella)、假交替单胞菌属(Pseudoalteromonas)、不动杆菌属(Acinetobacter)、海杆菌属(Marinobacter),其中以嗜冷杆菌属为主,其比例可达67%。从站位S11分离到的可培养锰细菌主要包括细菌域中变形杆菌门的α-变形杆菌纲(α-Proteobacteria)和γ-变形杆菌纲以及拟杆菌门(Bacteroides)中的黄杆菌纲(Flavobacteria);γ-变形杆菌纲主要包括希瓦氏菌属、海单胞菌属(Marinomonas)和交替单胞菌属(Alteromonas),α-变形杆菌纲主要为鞘氨醇单胞菌属(Sphingomonas)。实验菌株均对Mn2+有着较强的抗性,其中以菌株Marinomonas sp.S11-S-4耐受性最高。 The biogeochemical cycling of manganese is recognized as an important environmental process because manganese is not only an essential nutrient for all organisms but also its oxidation and reduction are intimately coupled with the cycling of other essential elements.Studies have demonstrated that Mn2+-oxidizing bacteria are abundant and distributed widely.A diverse array of bacteria,fungi,and microalgae have been shown to have the ability to catalyze oxidation or reduction of manganese.The oxidation of soluble Mn2+ to insoluble Mn3+/Mn4+ oxides and oxy-hydroxides is an environmentally important process because the solid-phase products oxidize a variety of organic and inorganic compounds,scavenge many metals,and serve as electron acceptors for anaerobic respiration.In most environments,Mn2+ oxidation is believed to be bact erially mediated.Over the years,Mn2+-oxidizing bacteria have been isolated from wide variety of environments,including marine and freshwaters,soils,sediments,water pipes,Mn nodules,and hydrothermal vents.Phylogenetically,Mn2+-oxidizing bacteria appear to be quite diverse,with all isolates analyzed to date falling within either the low G+C gram-positive bacteria,the Actinobacteria,or the α,β,and γ subgroups of the Proteobacteria branch of the domain Bacteria.In order to investigate the biodiversity of manganese bacteria in polar region,isolation,molecular identification and phylogenetic analysis of manganese bacteria were carried out in the sediments which were collected from Arctic ocean during 2nd Chinese Arctic Scientific Expedition.Twenty one and nineteen species of cultivable strain were isolated from the sediments of both station P11 and S11 respectively according to their distinct morphology on screening plate of manganese medium.Molecular identification and phylogenetic analysis showed that the cultivable manganese bacteria from station P11 were basically composed of γ subgroup of the Proteobacteria branch of the domain Bacteria(γ-Proteobacteria)and Actinobacteria,which accounted for 86% and 14% respectively.The γ-Proteobacteria mainly included Psychrobacter,Shewanella,Acinetobacter and Marinobacter,of which Psychrobacter was the major genus,it accounted for 67% of γ-Proteobacteria in sediments of station P11.The cultivable manganese bacteria from station S11 included α-proteobacteria,γ-Proteobacteria and Flavobacteria of Bacteroides.γ-Proteobacteria included Shewanella,Marinomonas and Alteromonas.The majority of α-Proteobacteria was Sphingomonas.The phylogenetic analysis indicated that bacteria from the sediments of station P11 and S11 had different cultivable manganese bacteria flora.All tested strains had higher resistance to Mn2+,of which Marinomonas sp.S11-S-4 had highest resistance. 国家自然科学基金资助项目(40576060)~